INEFFABLE JEWELLERY DALAM FOTOGRAFI PRODUK - Iqbal, T Muhammad; Kurniai, Benny; emas, cindi adelia puri (Institut Seni Indonesia Padangpanjang, 2026)
Ineffable is a brand located in the city of Padang which was founded by Nisrina Qurrata Aini and started in 2020 which still uses an online sales system, and then in 2022 ineffable started selling offline in shops in the city of Padang, its products presented by ineffable are various kinds of accessory products including; bracelets, necklaces, rings, hairpins, headbands and so on, the sales process uses a by order system. The aim of creating this work is to visualize and present Ineffable products in product photography. The creation of this work also uses theoretical foundations, namely, commercial photography, product photography, lighting and composition. The concept used in the creation of this work is using the summer concept. The creation method used is through a preparation process consisting of observation, literature study and interviews as well as design, namely a storyboard and finally embodiment. There are 20 works created in this final project which have the titles Boho Bracelet, Joy Neklace, Harmony of Rings and Natural Textures, Sand Beads, Ceria Necklace, Three Rings, Shell Bracelet, Sell Tie Braclece, Treasure Of the Sea, Sea Jewels, Mystic eye Breaclet, Crystals Bracelet, Cottagecore Necklace, Shoes Charm, Fir Bracelet, Sholace Charm, Wave Ribbon, Rona Ribbon, Ribbon Backrest.